Estimation of the Dependence of the Investment Multiplier on the Structure of the Regional Economy - Silvestrov, Sergey Nikolaevich; Bauer, Vladimir Petrovich; Eremin, Vladimir Vladimirovich (Economy of Regions, 2018)
The complicated conditions of the modern economy reduce the effectiveness of traditional instruments for economic regulation. The debt burden of the regions is growing, forcing them to cut spending on medicine and education, thereby, reducing investment in human capital, In these conditions, new economic tools for regional management are necessary, We propose the investment multiplier as such an instrument, The novelty of the research is the investigation of the impact of the investment multiplier on the regional economy as well as in developing an information model for analyzing the regional investment multiplier, We also have developed a model that allows to assess the relationship between the value of the investment multiplier and the structure of the regional economy, We consider the main directions of the analysis of the regional investment multiplier, allowing assessing its structure, dynamics and factors influencing its value, The model is based on the data of regional statistics, This model allows estimating the relationship between the value of the investment multiplier and the structure of the regional economy, We have made the assessment of this relationship for the Central and Far Eastern Federal Districts, The obtained results allowed to reveal the reserves for the economic development of these regions, as well as certain barriers on the way of this development, We have ranked the economic activities of the region by the strength of their influence on the value of the investment multiplier with a view to further managing this value, Applying the obtained results in managing the regional economy will help to avoid a significant deviation of the actual data from the planned values of the key indicators of the regional economy, Managing the value of the investment multiplier will help counteract the economic recession, initiating growth even in relatively difficult economic conditions,